The role of resilience in the relationship between exposure to trauma and suicide ideation - Venter, Nico (University of the Free State, 2017)
The relationship between exposure to trauma and suicide ideation has been established in literature. It is thus important to gain a better understanding of the factors than can buffer the negative outcomes of trauma exposures. Resilience is deemed to play a role in this regard and the aim of this study was to determine if resilience moderates the relationship between trauma exposure and suicide ideation. A total of 1001 adolescent participants from various schools across the Free State province participated in the study, with ages ranging from 14 to 16 years. A quantitative, correlational, non-experimental design was used. A hierarchical regression analysis was conducted to determine the role of resilience in the relationship between trauma exposure and suicide ideation. The results indicated that resilience does indeed moderate the relationship between trauma exposure and suicide ideation. Individuals with lower resilience score higher on suicide ideation. In contrast, individuals with high resilience revealed significantly lower scores on suicide ideation. These results can aid therapists in assisting clients to deal with trauma by focusing on the strengthening of their resilience.

Die verband tussen trauma en selfmoordideasie is reeds deur verskeie navorsingsartikels bewys. Dus is dit belangrik om’n beter begrip te verkry van die verskeie faktore wat as buffer kan optree teen negatiewe uitkomste nadat ’n individu aan trauma blootgestel is. Veerkragtigheid kan moontlik’n rol speel in dié opsig, en die doel van die studie was om te bepaal of veerkragtigheid die verhouding tussen blootstelling aan trauma en selfmoordideasie modereer. ’n Totaal van 1001 adolessente deelnemers van verskeie skole in die Vrystaat provinsie het aan die studie deelgeneem. Die ouderdomme het gewissel van 14 tot 16 jaar. Die studie het gebruik gemaak van ’n kwantitatiewe, korrelasionele, nie-eksperimentele ontwerp. ’n Hiërargiese regressie-analise is gedoen om te bepaal of veerkragtigheid ’n rol speel in die verhouding tussen blootstelling aan trauma en selfmoordideasie. Die resultate het aangedui dat veerkragtigheid die verhouding tussen blootstelling aan trauma en selfmoordideasie modereer. Individue met lae veerkragtigheid het hoër tellings in selfmoordideasie getoon. Daarteenoor het individue met hoë veerkragtigheid beduidende laer tellings van selfmoordideasie getoon. Na aanleiding van die resultate kan terapeute hul kliënte wat deur trauma geraak is,help deur op die versterking van veerkragtigheidte fokus.
Dissertation (M.A. (Psychology))--University of the Free State, 2017
Keywords: Resilience; Trauma exposure; Suicide ideation; Adolescence; Age; Free State Province; Resilience (Personality trait)